HOXB8 mediates resistance to cetuximab in colorectal cancer cells through activation of the STAT3 pathway - Yunan Liang; Han Lin; Zongsheng Jiang; Qi Zhao; Ri Cui; Shaotang Li (Discover Oncology)
Abstract Homeobox B8 (HOXB8) belongs to the HOX family and was essential to the development of colorectal carcinoma. Among the prevalent monoclonal antibodies for treating RAS/BRAF wild-type metastatic colorectal cancer (mCRC) patients, cetuximab stands out, but resistance to cetuximab frequently arises in targeted treatments. Currently, the role of HOXB8 in cetuximab-resistant mCRC remains unclear. By comparing drug-sensitive cell lines (SW48) with drug-resistant cell lines (HCT116, CACO2), we discovered that HOXB8 was substantially expressed in cetuximab-resistant cell lines, and furthermore, in drug-resistant cell lines (HCT116, CACO2), HOXB8 knockdown increased the cytotoxicity of cetuximab via blocking the signal transducer and activator of transcription 3 (STAT3) signaling pathway. Conversely, the excessive expression of HOXB8 reduced the growth suppression in SW48 cells caused by cetuximab by triggering the STAT3 signaling pathway. Conclusively, we conclude that HOXB8 has played an essential role in cetuximab-resistant mCRC and that treating HOXB8 specifically may be a useful treatment approach for certain cetuximab-resistant mCRC patients.